Yoga, the alpha and the omega : discourses on the yoga sutras of Patanjali - Osho, 1931-1990 (Rajneesh Foundation, 1976)
On an ancient treatise on the Hindu yoga system; lectures delivered in Bombay, December 1973-January 1974.